Antibodies to M-type phospholipase A2 receptor (PLA2R) in membranous lupus nephritis. (March 2019) - Garcia-Vives, E; Solé, C; Moliné, T; Alvarez-Rios, A M; Vidal, M; Agraz, I; Ordi-Ros, J; Cortés-Hernández, J
Background: Antibodies to M-type phospholipase A2 receptor (a-PLA2 R) have been identified in most patients with idiopathic membranous nephropathy, but the prevalence in membranous lupus nephritis (MLN) is still unclear. The objective of this study was to assess the prevalence of a-PLA2 R antibodies in a large cohort of patients with lupus nephritis. Methods: a-PLA2 R antibodies were measured by ELISA in serum from patients with systemic lupus erythematosus ( n  = 190), of whom 37 had a biopsy-proven MLN. Positive samples were confirmed by commercial ELISA kit, Western blot and immunohistochemistry in renal tissue. Results: A total of 10 from 190 patients (5.3%) with systemic lupus erythematosus had circulating a-PLA2 R measured by in-house ELISA assay. The antibodies were detected in 7 patients with MLN (18.9%) and 3 patients with non-renal lupus disease (3.2%). PLA2 R staining was detected in the kidney biopsy of 5 of the 7 (71.4%) patients with MLN. a-PLA2 R levels were associated with active disease but not proteinuria levels. Presence of a-PLA2 R antibodies at baseline was associated with worse remission rates and longer time to remission compared to those patients serologically negative. Conclusions: a-PLA2 R antibodies can be detected with low prevalence in MLN patients, but their detection is associated with a worse renal prognosis.